Ab initio calculations of the 2p3/2−2p1/2 fine-structure splitting in boronlike ions - Artemyev, Anton; Shabaev, V. M.; Tupitsyn, I. I.; Plunien, G.; Surzhykov, A.; Fritzsche, S. (Physical review. A, Atomic, molecular, and optical physics, 2013)
We have performed ab initio QED calculations of the (1s)2(2s)22p3/2−(1s)2(2s)22p1/2 fine-structure splitting along the boron isoelectronic sequence for all ions with 17≤Z≤100. This level splitting was evaluated within the extended Furry picture and by making use of four different screening potentials in order to estimate the effects of interelectronic correlations. The accuracy of the predicted transition energies has been improved significantly when compared with previous computations.